Controlling Rice Leaf Breaking Force by Temperature and Moisture Content to Reduce Breakage - Zhong Tang; Yu Li; Ben Zhang; Meilin Wang; Yaoming Li (Agronomy, 2020)
Leaf fragments and grain mixture produced by rice threshing with a combine harvester seriously affects the subsequent grain cleaning efficiency. In this paper, rice leaf breaking force was tested at different temperatures and moisture contents to analyze the influence of temperature on the tensile properties of rice leaves. The overlapping regions of rice leaf breaking force and grain separation force at different temperatures were obtained. Based on the rice leaf breaking force, the effect of the temperature change on rice leaf with different moisture content was analyzed. The results showed that tensile strength of rice leaf decreased first, then increased and finally decreased from rice sheath to the top. The tensile breaking force of the leaf sheath was about 75 N (N is Newton, 1 N = 1 kg·m/s²). The tensile fracture resistance of rice leaf was shown to weaken with the increase of temperature. The influence of the moisture content on the mechanical properties of rice leaf during the process of temperature change was small. At 30 to 35 °C, the blade was the strongest tensile fracture resistance, which was the lowest probability of fracture under the same stress condition. At this time, the rice grain separation force has the least coincidence with the rice leaf resistance to breakage. According to the breaking force of different blade layers, the number of blade layers has a significant linear relationship with its tensile limit. Therefore, the overall fracture resistance of the multilayer blade can be improved by controlling the temperature and moisture content.